2022
DOI: 10.18662/rrem/14.4sup1/673
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Students’ Sense of Belonging, Grit and Anxiety during Pandemic Times

Abstract: Covid-19 restrictions in Italy have significantly reduced the ‘in-presence’ time spent with classmates and teachers. As a result, this new way of relating to one another has challenged many students by increasing anxiety and depression. In such reality, protective factors such as sense of belonging (SB) and Grit (GR) can reduce anxiety (ANX).  Considering the pandemic context,  the scope of this study is to explore the relationship between SB/GR and ANX, as a risk factor and to understand whether the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have observed a concerning rise in depression and anxiety among teenagers and young adults, leading to decreased levels of life satisfaction. These issues have notably intensified following the onset of the pandemic (Lattke et al, 2022; Preetz et al, 2021). At this point, it is crucial to develop resilience, as it is a determinant of the life satisfaction of adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have observed a concerning rise in depression and anxiety among teenagers and young adults, leading to decreased levels of life satisfaction. These issues have notably intensified following the onset of the pandemic (Lattke et al, 2022; Preetz et al, 2021). At this point, it is crucial to develop resilience, as it is a determinant of the life satisfaction of adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have observed a concerning rise in depression and anxiety among teenagers and young adults, leading to decreased levels of life satisfaction. These issues have notably intensified following the onset of the pandemic [ 18 , 19 ]. Studies examining this situation have shown that resilience and hope are effective factors in predicting stress arising from the Pandemic [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two years after the spread of COVID-19, young people are the most affected population group (32)(33)(34). Studies from the last 2 years show that adolescents and young adults are experiencing worrying levels of depression, anxiety and lower life satisfaction, with mental health problems increasing significantly in adolescents compared to pre-pandemic levels (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%